2018
DOI: 10.1007/s10792-018-0953-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ocular surface status after phacoemulsification in patients with senile cataract

Abstract: There is a transient deterioration of "dry eye" status post-phacoemulsification. The patients should be carefully counselled about the evanescent nature of the disease. Incision can be given at the site of high corneal curvature to neutralize astigmatism without any fear of inducing dry eye. Minimum light exposure and ultrasound energy should be used during the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
4
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 35 publications
5
60
4
6
Order By: Relevance
“…Similar results were obtained in study by Kasetsuwan N et al 3 The study conducted by Kohli P et al also showed an increase in values postoperatively, similar to our study. 8 When compared to the previous studies in the literature, patients falling under dry eye criteria postoperatively were less in our study. This could be because of the difference in the size and site of incision.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Similar results were obtained in study by Kasetsuwan N et al 3 The study conducted by Kohli P et al also showed an increase in values postoperatively, similar to our study. 8 When compared to the previous studies in the literature, patients falling under dry eye criteria postoperatively were less in our study. This could be because of the difference in the size and site of incision.…”
Section: Discussioncontrasting
confidence: 54%
“…The phototoxic effect of the light of operating microscope causes production of reactive oxygen species, leading to devitalization of conjunctival cells and decrease in conjunctival goblet cell density. 8 Conventional topical therapy following cataract surgery includes topical corticosteroids (to manage inflammation) and antibiotics. 2 Topical corticosteroids commonly used postoperatively are dexamethasone and betamethasone in the form of drops and bed time ointment.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report by DEWS recommends non-invasive diagnostic tests [19]. Nevertheless, TBUT, together with the OSDI scores and Schirmer I test, is still the most commonly used parameter to ascertain the presence of DED and monitor its changes over time [20,21]. Our study population undergoing cataract surgery had similar features to that of previous studies [20,21].…”
Section: Discussionmentioning
confidence: 60%
“…Nevertheless, TBUT, together with the OSDI scores and Schirmer I test, is still the most commonly used parameter to ascertain the presence of DED and monitor its changes over time [20,21]. Our study population undergoing cataract surgery had similar features to that of previous studies [20,21]. Of the whole study population, individuals with normal ocular surfaces (TBUT [ 7 s) and no relevant DED symptoms (OSDI B 12) were just 38% at baseline.…”
Section: Discussionmentioning
confidence: 85%
“…However, in a prospective study of 50 patients by Kohli et al. 15 and a retrospective study of 96 patients by Cetinkaya et al., 16 the signs and symptoms of DED appeared to return to pre-operative levels at 3 months.…”
Section: Prevalence Of Cataract Surgery Associated Dedmentioning
confidence: 92%